Meningkatkan Hasil Belajar Siswa Dengan Model Project Based Learning di SMA Islam Kandangan - Hossain, Fiza Amrina; Haryanto, Sri; Firdaus, Firdaus (Jurnal Ilmiah Dikdaya, 2023)
There are many problems from students related to physics concepts, this is because students are dependent on phones which makes students inattentive to dig up information about Learning, the learning process can be concluded less interest, attention, and less attractive to students' because there is no learning media which can attract students to be interested in the material presented. Therefore necessary to create innovation in learning process so students can re-express the concepts they have learned and able to apply it, one of them is implementing a project-based learning model using global warming simulations. This thesis aims to enhance student learning outcomes using project-based learning models, find student responses, and implement project-based learning models.Â  This thesis use quantitative experiment method where design of research is nonequivalent group design. Data collection techniques Use methods of documentation, observation, questionnaires, and test questions. The results show that: 1) Implementation of project based learning models using global warming simulations can improve students' soft skills and psychomotor abilities; 2) Project based learning model using global warming simulation improves learning outcomes seen in The experimental class has a mean of 88.31, the control class has a mean of 74, and the n-gain score of the experimental class is 80.62%, meaning they are in the valid categories; 3) Implementation of project based learning models using global warming simulations got a satisfactory response, as many as 6 students (18.75%) gave a good response, 20 students (65.62%) gave a satisfactory response, 5 students (15 .62%) gave a less than satisfactory response.